Uslub Muqābalah Surat Al-Lail: Pendekatan Ilmu Badi’ dan Teori Relevansi - Husni, Ahmad; Sopian, Asep; Nurmala, Mia (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose-This study aims to explore the use of uslūb muqābalah in Surah Al-Lail by combining the classical badī' approach and the theory of relevance of modern cognitive linguistics. The beauty of muqābalah will be difficult to understand by those who do not understand the meaning of the Qur'an because its charm lies in the depth of the meaning of its verses.  Design/Methodology/Approach- The research uses qualitative discourse analysis based on literature studies and contextual interpretation of muqābalah verses. The focus of the study is the process of pairing opposing meanings forming rhetorical structures and cognitive devices in the delivery of implicit messages. Findings—The results of the study show that the pattern of couples in Surah Al-Lail, such as night and day, giving and file, strengthens aesthetic beauty while optimizing the relevance of meaning. The principle of optimal relevance encourages the inferential drawing of moral conclusions with minimal cognitive effort. Research Limitation/Implications- This research is limited to Surah Al-Lail and does not compare it with other suras. However, this study contributes to developing an interdisciplinary approach between balāghah and pragmatic linguistics, which is useful for innovation in the teaching of tafsir and Arabic.